Reducing Surface Wetness Leads to Tropical Hydrological Cycle Regime Transition. Issue 8 (25th April 2021) - Fan, Bowen; Tan, Zhihong; Shaw, Tiffany A.; Kite, Edwin S.
Abstract: Earth's modern climate is characterized by wet, rainy deep tropics, however, paleoclimate and planetary science have revealed a wide range of hydrological cycle regimes connected to different external parameters. Here we investigate how surface wetness affects the tropical hydrological cycle. When surface wetness is decreased in an Earth‐like general circulation model, the tropics remain wet but the transition from a rainy to a rain‐free regime. The rain‐free regime occurs when surface precipitation is suppressed as negative evaporation (surface condensation) balances moisture flux convergence. The regime transition is dominated by near‐surface relative humidity changes in contrast to the hypothesis that relative humidity changes are small. We show near‐surface relative humidity changes responsible for the regime transition are controlled by re‐evaporation of stratiform precipitation near the lifting condensation level. Re‐evaporation impacts the near‐surface through vertical mixing. Our results reveal a new rain‐free tropical hydrological cycle regime that goes beyond the wet/dry paradigm. Plain Language Summary: Paleoclimatology and planetary science have revealed a range of tropical climates, for example, the Earth's modern deep tropics are wet and rainy, whereas the tropics of Snowball Earth and Titan are drier. Previous work showed a range of external parameter affects the tropical hydrological cycle. Here we quantify how surface wetness alone affects the tropical hydrological cycle. In response to reduced surface wetness in an Earth‐like general circulation model, the tropics remain wet but the transition from a rainy to a rain‐free regime at the surface. The regime transition is controlled by the re‐evaporation of rain near the cloud base. In the rain‐free regime, tropical rainfall is re‐evaporated aloft and impact near‐surface through vertical mixing, increasing the relative humidity. The surface evaporation becomes negative (surface condensation occurs) because the near‐surface air is wetter than the dry surface. Our results reveal a new tropical hydrological cycle regime that is wet but rain‐free at the surface and shows wet/dry is not sufficient to characterize the tropics. Key Points: When surface wetness is reduced in a general circulation model, the tropics transition from rainy to the rain‐free surface regime Re‐evaporation of stratiform precipitation causes the regime transition by impacting near‐surface relative humidity Re‐evaporation happens at the cloud base and impacts the near surface through vertical mixing